2019
DOI: 10.1210/clinem/dgz216
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in LAMB2 Are Associated With Albuminuria and Optic Nerve Hypoplasia With Hypopituitarism

Abstract: Context Mutations in LAMB2, encoding the basement membrane protein, laminin β2, are associated with an autosomal recessive disorder characterized by congenital nephrotic syndrome, ocular abnormalities, and neurodevelopmental delay (Pierson syndrome). Case description This report describes a 12-year-old boy with short stature, visual impairment, and developmental delay who presented with macroscopic hematuria and albuminuria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Although hypothyroidism may be a consequence of the urinary loss of thyroid binding globulin as a part of nephrotic proteinuria, it occurred in our patient only after the second nephrectomy. As secondary reasons were excluded, it could be hypothetically related to the primary disease as laminin isoforms are expressed throughout the pituitary development and may lead to hypopituitarism with growth hormone deficiency [9]. We also suspected an impact of PIERSS on disturbed erythropoiesis in our patient who presented with unexplained erythropoietin-resistant anemia either after KTx.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although hypothyroidism may be a consequence of the urinary loss of thyroid binding globulin as a part of nephrotic proteinuria, it occurred in our patient only after the second nephrectomy. As secondary reasons were excluded, it could be hypothetically related to the primary disease as laminin isoforms are expressed throughout the pituitary development and may lead to hypopituitarism with growth hormone deficiency [9]. We also suspected an impact of PIERSS on disturbed erythropoiesis in our patient who presented with unexplained erythropoietin-resistant anemia either after KTx.…”
Section: Discussionmentioning
confidence: 92%
“…The most representative and relatively constant ocular anomaly in PIERSS is congenital microcoria caused by hypoplasia or aplasia of the dilator muscles of the iris [20]. It is a part of the wide spectrum of other ophthalmological features in PIERSS, including lens anomalies (cataract, abnormal lens shape, and posterior lenticonus), nystagmus, optic nerve hypoplasia, posterior embryotoxon, megalocornea, and retinal defects [3,9,18,20]. They are related to the failed LMβ2 expression in ocular structures during eye organogenesis [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports showed that patients with biallelic putative LAMB2 truncating variants exhibited a complete lack of renal laminin beta‐2 expression, whereas those with presumed non‐truncating LAMB2 variants on at least one allele showed residual or even normal glomerular expression of laminin beta‐2 (Maselli et al, 2009 ; Tahoun et al, 2020 ; Zenker et al, 2004 ). A similar phenomenon was observed in our patient with biallelic LAMB2 truncating variants.…”
Section: Discussionmentioning
confidence: 99%
“…LAMB2 variants cause congenital nephrosis with mesangial sclerosis and optical abnormalities ( 35 ). In 2020, compound heterozygous missense mutations identified in LAMB2 (c.737G>A [p.Arg246Gln] and c.3982G>C [p.Gly1328Arg]) were detected in a patient with isolated GH deficiency and global developmental delay, hypoplastic anterior pituitary, optic nerve hypoplasia, and corpus callosum dysgenesis ( 8 ). The details have not been investigated, but the pituitary glands of Lamb2 –/– mice were found to have abnormal cellular clusters.…”
Section: Novel Genes and Variants Identified By High-throughput Analysismentioning
confidence: 99%